Thermodynamic properties and hydration behavior of ye'elimite. (December 2022) - Lothenbach, B.; Geiger, C.A.; Dachs, E.; Winnefeld, F.; Pisch, A.
Abstract: Ye'elimite occurs in nature and in calcium sulfoaluminate cements. The thermodynamic properties of synthetic orthorhombic ye'elimite, Ca4 Al6 O12 SO4, were determined experimentally using low-temperature relaxation calorimetry and at higher temperatures using differential scanning calorimetry and drop calorimetry. The heat capacity, C p, of 480 J/mol/K and standard entropy, S°, of 487 J/mol/K at 298 K were measured. These values compare well with those calculated by density functional theory. Heat of dissolution measurements give an enthalpy of formation, Δf H°, of −8382.5 kJ/mol for ye'elimite. Heat of reaction measurements for nanocrystalline Al(OH)3 give Δf H° = −1276 kJ/mol. The resulting calorimetric-based enthalpies were used to calculate the degree of ye'elemite hydration. A solubility product, KS0, ye'elimite, of 10 −1.4 at 298 K was calculated from the enthalpy and entropy values. Pore solution composition indicates the presence of a hydroxylated surface layer on ye'elimite, which results in a lower solubility with KS0, surface ≈10 19 for the reaction Ca4 Al6 O12 SO4 + 12H2 O 0 → 4Ca 2+ + 6Al(OH)4 − + SO4 2− .